Sedimentology and Facies Analysis of the Pedawan Formation along Borneo Heights road, Siburan Area, Kuching, Sarawak, Malaysia - Samsudin, N.M. (Slovnaft VURUP a.s, 2021)
Several outcrops of Pedawan Formation (Jurassic - Cretaceous age) found along the Borneo Heights road in the Siburan area were evaluated. Detailed facies analysis of four (4) outcrops were undertaken, and seven (7) lithofacies were identified. These are, i) S1: Massive, ungraded medium-grained sandstone, ii) S2: Graded, coarse to fine-grained sandstone (turbidite sequence, Ta-Tb), iii) S3: Thick, medium to fine-grained sandstone with mudstone interbeds, iv) S4: Thick, laminated medium to finegrained sandstone with floating mud clasts, v) S5: Massive slumping structure of medium-grained sandstones with thin mudstone layers, vi) M1: Massive, laminated thin mudstone with medium to fine sandstone interbeds, and lastly, vii) M2: Thick mudstone with thin, fine to medium-grained sandstone interbeds. The lithofacies are grouped into five facies associations, which are; i) FA1: Slope - cohesive flow deposits and slump structure, ii) FA2: Canyon floor filled with high to low-density debrites and turbidites, iii) FA3: Distributary turbidite channel, iv) FA4: Lobe fringe - fine to medium-grained sandstone with thick mudstone, and v) FA5: Thin mudstone and sandstone interbed of the basinal plain. The overall depositional environment is interpreted to be the slope to the fan lobe area of the deep marine setting. Based on a paleontological analysis, six (6) species of microfossils are determined and mostly deposited in benthic marine depositional environments. Â© 2021. All Rights Reserved.